Evaluating the addition of bevacizumab to endocrine therapy as first-line treatment for hormone receptor–positive metastatic breast cancer: a pooled analysis from the LEA (GEICAM/2006-11_GBG51) and CALGB 40503 (Alliance) trials. (August 2019) - Martín, M.; Loibl, S.; Hyslop, T.; De la Haba-Rodríguez, J.; Aktas, B.; Cirrincione, C.T.; Mehta, K.; Barry, W.T.; Morales, S.; Carey, L.A.; Garcia-Saenz, J.A.; Partridge, A.; et al.
Abstract: Background: Randomised trials comparing the efficacy of standard endocrine therapy (ET) versus experimental ET + bevacizumab (Bev) in 1st line hormone receptor–positive patients with metastatic breast cancer have thus far shown conflicting results. Patients and methods: We pooled data from two similar phase III randomised trials of ET ± Bev (LEA and Cancer and Leukemia Group B 40503) to increase precision in estimating treatment effect. Primary end-point was progression-free survival (PFS). Secondary end-points were overall survival (OS), objective response rate (ORR), clinical benefit rate (CBR) and safety. Exploratory analyses were performed within subgroups defined by patients with recurrent disease, de novo disease, prior endocrine sensitivity or resistance and reported grades III–IV hypertension and proteinuria. Results: The pooled sample consisted of 749 patients randomised to ET or ET + Bev. Median PFS was 14.3 months for ET versus 19 months for ET + Bev (unadjusted hazard ratio [HR] 0.77; 95% confidence interval [CI] 0.66–0.91; p < 0.01). ORR and CBR with ET and ET + Bev were 40 versus 61% (p < 0.01) and 64 versus 77% (p < 0.01), respectively. There was no difference in OS (HR 0.96; 95% CI 0.77–1.18; p = 0.68). PFS was superior for ET + Bev for endocrine-sensitive patients (HR 0.68; 95% CI 0.53–0.89; p = 0.004). Grade III–IV hypertension (2.2 versus 20.1%), proteinuria (0 versus 9.3%), cardiovascular (0.5 versus 4.2%) and liver events (0 versus 2.9%) were significantly higher for ET + Bev (all p < 0.01). Hypertension and proteinuria were not predictors of efficacy (interaction test p = 0.33). Conclusion: The addition of Bev to ET increased PFS overall and in endocrine-sensitive patients but not OS at the expense of significant additional toxicity. Trials registration: ClinicalTrial.Gov NCT00545077 and NCT00601900. Highlights: Bevacizumab plus endocrine therapy increased progression-free survival overall. Bevacizumab plus endocrine therapy does not increased overall survival. This combination adds significant toxicity. This should not be recommended for 1st line HR+/HER2-advanced breast cancer. Hypertension and proteinuria are not predictive of bevacizumab efficacy.